2019
DOI: 10.1080/1359432x.2019.1678588
|View full text |Cite
|
Sign up to set email alerts
|

Investigating follower felt trust from a social cognitive perspective

Abstract: through which followers' felt trust influences their in-role and extra-role performance. Based on social cognitive theory, we proposed that occupational self-efficacy (OSE) mediates the felt trust-performance relationship in workplace settings, and tested these relationships in two empirical studies. Study 1 was a cross-sectional pre-study (N = 189) investigating only the mediating effects of OSE. For the main study, i.e., Study 2 (N = 500), we collected data at three different measurement occasions to minimiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 68 publications
4
29
0
Order By: Relevance
“…Specifically, leaders' reliance on employees at work is based on positive judgements about employees' abilities and skills (Gillespie, 2003). Zheng et al (2019) also found that felt reliance was positively related to self-perceived competence. In addition, employees who are relied upon may obtain job autonomy because leaders will assign important tasks to them and allow them more control and decision latitude (Brower et al, 2009;Skiba and Wildman, 2019).…”
Section: The Mediating Effect Of Intrinsic Motivationmentioning
confidence: 84%
See 4 more Smart Citations
“…Specifically, leaders' reliance on employees at work is based on positive judgements about employees' abilities and skills (Gillespie, 2003). Zheng et al (2019) also found that felt reliance was positively related to self-perceived competence. In addition, employees who are relied upon may obtain job autonomy because leaders will assign important tasks to them and allow them more control and decision latitude (Brower et al, 2009;Skiba and Wildman, 2019).…”
Section: The Mediating Effect Of Intrinsic Motivationmentioning
confidence: 84%
“…Although felt trust was positively related to in-role and extra-role performance (Zheng et al, 2019), whether and how it affects voice behaviour remains underexplored, and little is known about the two dimensions of felt trust. In addressing these questions, we propose and test a mediation model that felt trust (felt reliance and felt disclosure) positively affects voice behaviour through felt obligation and intrinsic motivation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations